Association Between Glaucoma and the Risk of Dementia. Issue 7 (February 2016) - Su, Cheng-Wen; Lin, Che-Chen; Kao, Chia-Hung; Chen, Hsin-Yi
Abstract : Abstract: We investigated the association of primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG) with the risk of dementia by evaluating their clinical and epidemiological similarities by using a nationally representative sample in Taiwan. Data were collected from the National Health Insurance Research Database of Taiwan. In total, 6509 patients with glaucoma (3304 with POAG and 3205 with PACG) were enrolled, and a comparison cohort of 26, 036 individuals without glaucoma was established after matching for age and sex. The cumulative incidence curve of overall dementia for each cohort was evaluated. The risk of dementia was analyzed using univariate and multivariate Cox proportional hazard models after adjustment for demographic characteristics and comorbidities. The patients with glaucoma exhibited a significantly higher risk of dementia than the individuals without glaucoma did (hazard ratio [HR] = 1.13, 95% confidence interval [CI] = 1.01–1.27). The patients with POAG exhibited a 1.21-fold increased risk of dementia compared with the individuals without glaucoma (HR = 1.21, 95% CI = 1.02–1.43). However, the patients with PACG were not significantly associated with an increased risk of dementia compared with the individuals without glaucoma (HR = 1.09, 95% CI = 0.95–1.26). Patients with POAG aged ≥65 years were significantly associated with an increased risk of dementia compared with the individuals without glaucoma (HR = 1.28, 95% CI = 1.07–1.54). Females with POAG exhibited a 1.34-fold increased risk of dementia compared with females without glaucoma (95% CI = 1.06–1.69). This study demonstrated that patients with POAG but not those with PACG were associated with an increased risk of dementia compared with the general population.